PD-L1 Test-Based Strategy With Nivolumab as the Second-Line Treatment in Advanced NSCLC： A Cost-Effectiveness Analysis in China - Liu, Qiao; Luo, Xia; Zhou, Zhen; Peng, Liubao; Yi, Lidan; Wan, Xiaomin; Tan, Chongqing; Zeng, Xiaohui (Frontiers in Oncology, 2021)
Objective Our previous economic assessment found that nivolumab was not cost-effective for Chinese patients with advanced non-small cell lung cancer (NSCLC) and without EGFR mutations or ALK translocations, when compared with the standard second-line drug docetaxel. However, a greater survival benefit with nivolumab was observed for patients with 1% or greater tumor programmed death ligand 1 (PD-L1) expression. In terms of this, the present analysis was designed to explore whether it is cost-effective to use the PD-L1 test to guide second-line nivolumab treatment in China. Material and Methods A Markov model was established to project the lifetime costs and quality-adjusted life-years (QALYs) of three second-line treatment strategies: two no PD-L1 test strategies (nivolumab and docetaxel and strategies without a PD-L1 test), and one PD-L1 test-based strategy. Deterministic and probabilistic sensitivity analyses were performed to examine the robustness of our results. Additional price reduction and willingness-to-pay (WTP) threshold scenario analyses were performed to explore the impact of economic and health policies with Chinese characteristics on our results. Results The PD-L1 test-based strategy cost approximately CNY 194,607 (USD 28,210) more and yielded an additional 0.27 QALYs compared to the docetaxel strategy without a PD-L1 test, equating an incremental cost-effectiveness ratio (ICER) of CNY 731,089 (USD 105,978)/QALY. Deterministic sensitivity analyses showed that the price of nivolumab was the strongest source of variation in the ICERs. Probability sensitivity analysis showed that the probability for the PD-L1 test-based strategy being cost-effective increases with the increase of WTP thresholds. Conclusion From the perspective of the Chinese healthcare system, using PD-L1 test to guide second-line nivolumab treatment was not cost-effective. The National Healthcare Security Administration negotiation on the price reduction of nivolumab was found to be the most effective action to improve its cost-effectiveness in China.